Pengaruh Profitabilitas, Leverage, Kepemilikan Institusional, Dan Investment Opportunity Set Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2010-2014 - Sriwahyuni, Ulfa; SP, Wihandaru (Jurnal Manajemen Bisnis, 2016)
The research aims to test the profitability, leverage, institutional ownership, and the investment opportunity set (IOS) toward firm value with dividend policy as an intervening variable. The sample is taken from the manufacture companies listed on Indonesia Stock Market or Bursa Efek Indonesia (BEI) during 2010-2014. This study used purposive sampling method. The data analysis technique in this research was conducted using multiple linear regression. The analysis method used classical assumption test, composed from; heteroskedasticity test, multicollinearity test, and autocorrelation test. The hypothesis used T-Test, F-Test, and Determinant Coefficient Test. The result shows that profitability, leverage, investment opportunity set (IOS) and dividend policy are significantly influence on firm value. Meanwhile institutional ownership is not significantly influence on firm value. Profitability, institutional ownership, and investment opportunity set (IOS) are significantly influenced on dividend policy. Leverage is not significantly influenced on dividend policy. Lastly, dividend policy can be an intervening variable from profitability, institutional ownership, and investment opportunity set (IOS)